Exercise Training Protects Cardiomyocytes from Deleterious Effects of Palmitate - Alves, Marcia Netto Magalhães; Roman-Campos, Danilo; Parreira, Amanda B.; Almeida, Pedro W. M.; Cruz, Jader Santos; Guatimosim, Silvia; Dias-Peixoto, Marco Fabricio (International Journal of Sports Medicine, 2017)
We investigated the effects of palmitate, a high saturated fat, on Ca2+, action potential and reactive oxygen species dynamics in cardiomyocytes from untrained and trained mice. Male mice were subjected to moderate intensity exercise training on a treadmill. Cardiomyocytes of untrained and trained mice were isolated, treated for 30 min with palmitate and intracellular calcium transient and action potential duration were recorded. Additionally, we assessed reactive oxygen species generation. Treatment of cardiomyocytes from untrained mice with palmitate induced a significant decrease in Ca2+ transient magnitude by 34%. Exercise training did not change cardiomyocyte Ca2+ dynamics in the control group. However, trained cardiomyocytes were protected from deleterious effects of palmitate. Action potential duration was not altered by palmitate in either untrained or trained cardiomyocytes. Moreover, palmitate treatment increased reactive oxygen species generation in both untrained and trained cardiomyocytes. Nevertheless, the levels of reactive oxygen species in trained cardiomyocytes treated with palmitate were still 27% lower than those seen at basal conditions in untrained cardiomyocytes. Taken together, these findings indicate that exercise training protects cardiomyocytes from deleterious effects of palmitate possibly by inhibiting exacerbated ROS production.
Keywords: cardiomyocyte dysfunction; saturated fatty acids; exercise training; calcium transient; reactive oxygen species